2016
DOI: 10.18632/oncotarget.9343
|View full text |Cite
|
Sign up to set email alerts
|

HEY2, a target of miR-137, indicates poor outcomes and promotes cell proliferation and migration in hepatocellular carcinoma

Abstract: HEY2, a bHLH transcription factor, has been implicated in the progression of human cancers. Here, we showed that HEY2 expression was markedly increased in HCC, compared with the adjacent nontumorous tissues. High HEY2 expression was closely correlated with tumor multiplicity, tumor differentiation and TNM stage. Kaplan-Meier analyses revealed that HEY2 expression was significantly associated with poor overall and disease-free survival in a training cohort of 361 patients with HCC. The prognostic implication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
(31 reference statements)
0
24
0
Order By: Relevance
“…Liang et al ( 12 ) reported that downregulation of miR-137 promoted cell proliferation in pediatric high-grade gliomas. Furthermore, the suppressive role of miR-137 in HCC has gradually been elucidated ( 13 ). Liu et al ( 14 ) reported that miR-137 suppresses tumor growth and metastasis in HCC by targeting AKT serine/threonine kinase 2.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al ( 12 ) reported that downregulation of miR-137 promoted cell proliferation in pediatric high-grade gliomas. Furthermore, the suppressive role of miR-137 in HCC has gradually been elucidated ( 13 ). Liu et al ( 14 ) reported that miR-137 suppresses tumor growth and metastasis in HCC by targeting AKT serine/threonine kinase 2.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, miR-34a was found to promote proliferation of human pulmonary artery smooth muscle cells by targeting platelet-derived growth factor alpha [ 15 ], and miR-181b activated the PI3K and MAPK signaling pathways, which subsequently promoted VSMCs proliferation [ 16 ]. Recently, miR-137 was found to play tumor-suppressive roles in the different types of cancers [ 17 ā€“ 20 ]. However, it is unclear whether miR-137 plays a role in the VSMCs proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found that miR-98 was upregulated in rabbit brains during the progression of AD-like pathology, consistent with previous reports that miR-98 was upregulated in AD mouse models ( 38 ). Furthermore, during zebrafish arteriovenous differentiation, Sox18 and Sox7 induced HEY2 ortholog gridlock, and a high expression of HEY2 has been found in other diseases, indicating that HEY2 may inhibit cell differentiation ( 21 ). However, miR-98 contributed to inhibition of the expression of HEY2 and the Notch signaling pathway in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signals are transferred among adjacent cells through Notch receptors and their ligands that regulate differentiation, proliferation and apoptosis in several cell types, including stem cells ( 20 ). Hairy and enhancer of split (Hes)-related with YRPW motif protein 2 (HEY2), a hairy-related transcription factor family of Notch-downstream transcriptional repressors, has indispensable and complementary functions for the development of blood vessels ( 21 , 22 ). MicroRNAs (miRs) are small non-coding RNAs that regulate protein output post-transcriptionally, and each biological process is associated with miRNA-dependent regulation ( 23 ).…”
Section: Introductionmentioning
confidence: 99%